Gene polymorphisms as risk factors for predicting the cardiovascular manifestations in Marfan syndrome - Benke, Kálmán; Ágg, Bence; Mátyás, Gábor; Szokolai, Viola; Harsányi, Gergely; Szilveszter, Bálint; Odler, Balázs; Pólos, Miklós; Maurovich-Horvat, Pál; Radovits, Tamás; Merkely, Béla; Nagy, Zsolt B.; Szabolcs, Zoltán (Thrombosis and Haemostasis, 2015)
Folic acid metabolism enzyme polymorphisms are believed to be responsible for the elevation of homocysteine (HCY) concentration in the blood plasma, correlating with the pathogenesis of aortic aneurysms and aortic dissection. We studied 71 Marfan patients divided into groups based on the severity of cardiovascular involvement: no intervention required (n=27, Group A); mild involvement requiring intervention (n=17, Group B); severe involvement (n=27, Group C) subdivided into aortic dilatation (n=14, Group C1) and aortic dissection (n=13, Group C2), as well as 117 control subjects. We evaluated HCY, folate, vitamin B12 and the polymorphisms of methylenetetrahydrofo-late reductase (MTHFR;c.665C>T and c.1286A>C), methionine synthase (MTR;c.2756A>G) and methionine synthase reductase (MTRR;c.66A>G). Multiple comparisons showed significantly higher levels of HCY in Group C2 compared to Groups A, B, C1 and control group (p< 0.0001, p< 0.0001, p=0.001 and p=0.003, respectively). Fo-late was lower in Group C2 than in Groups A, B, C1 and control subjects (p< 0.0001, p=0.02, p< 0.0001 and p< 0.0001, respectively). Group C2 had the highest prevalence of homozygotes for all four gene polymorphisms. Multivariate logistic regression analysis revealed that HCY plasma level was an independent risk factor for severe cardiovascular involvement (Group C; odds ratio [OR] 1.85, 95 % confidence interval [CI] 1.28–2.67, p=0.001) as well as for aortic dissection (Group C2; OR 2.49, 95 %CI 1.30–4.78, p=0.006). In conclusion, severe cardiovascular involvement in Marfan patients, and especially aortic dissection, is associated with higher HCY plasma levels and prevalence of homozygous genotypes of folic acid metabolism enzymes than mild or no cardiovascular involvement. These results suggest that impaired folic acid metabolism has an important role in the development and remodelling of the extracellular matrix of the aorta.
Keywords: Cardiology; vascular remodelling; single nucleotide polymorphism; HCY; matrix-metalloproteinases